Genetic evidence that bound coagulase of Staphylococcus aureus is not clumping factor - FOSTER, TIMOTHY (My University, 1992)
Staphylococcus aureus Newman cells carry a surface receptor for fibrinogen called clumping factor. The bacteria also express coagulase, an extracellular protein that binds to prothrombin to form a complex with thrombinlike activity which coverts fibrinogen to fibrin. We have confirmed a recent report (M. K. Bodén and J.-I. Flock, Infect. Immun. 57:2358-2363, 1989) that coagulase can bind to fibrinogen as well as to prothrombin and also that a fraction of coagulase is firmly attached to the cell. A mutant with a deletion in the chromosomal coa gene was isolated by allelic replacement. Allelic replacement either was directly selected by electrotransformation of S. aureus R3N4220 with a nonreplicating suicide plasmid, pCOA18, carrying the delta coa::Tcr mutation or occurred after transduction of the integrated pCOA18 plasmid. The coa mutant was completely devoid of coagulase activity but interacted both with soluble fibrinogen and with solid-phase fibrinogen with the same avidity as the parental strain. This strongly suggests that the bound form of coagulase is not clumping factor and is not responsible for the adherence of S. aureus Newman to solid-phase fibrinogen. The fibrinogen binding determinant of coagulase was located in the C terminus of the protein, by analyzing truncated fusion proteins, in contrast to the prothrombin-binding region which was located in the N terminus.